Lung cancer, comorbidities, and medication: the infernal trio - Hélène Pluchart; Hélène Pluchart; Hélène Pluchart; Sébastien Chanoine; Sébastien Chanoine; Sébastien Chanoine; Denis Moro-Sibilot; Denis Moro-Sibilot; Denis Moro-Sibilot; Christos Chouaid; Christos Chouaid; Gil Frey; et al. (Frontiers Media S.A., 2024)
Most patients with lung cancer are smokers and are of advanced age. They are therefore at high risk of having age- and lifestyle-related comorbidities. These comorbidities are subject to treatment or even polypharmacy. There is growing evidence of a link between lung cancer, comorbidities and medications. The relationships between these entities are complex. The presence of comorbidities and their treatments influence the time of cancer diagnosis, as well as the diagnostic and treatment strategy. On the other hand, cancer treatment may have an impact on the patient's comorbidities such as renal failure, pneumonitis or endocrinopathies. This review highlights how some comorbidities may have an impact on lung cancer presentation and may require treatment adjustments. Reciprocal influences between the treatment of comorbidities and anticancer therapy will also be discussed.